Research Programs of I. Lakatos in the Context of the Information Society - O. E. Baksansky; I. A. Emelin (Сеченовский вестник)
The article attempts to describe the concept of development and change of research programs of the hungarian scientist Imre Lakatos, to defi ne features of his scientifi c methodology and his views on the history and philosophy of science in the context of the information society.